2006
DOI: 10.21000/jasmr06021657
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a Strategic Review of Ard Risk in Rio Tinto

Abstract: Following an internal review of significant environmental risks in 2003, Rio Tinto developed, using a combination of in-house and external expertise, an ARD screening protocol to rank innate hazards at its mines and a second protocol to assess performance in key management areas during site-based risk reviews. Eight risk reviews were conducted in 2004 and another four in early 2005, at mines covering a wide range of commodities, operating methods and project stages. These reviews have proven successful in iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This process can be strongly catalysed by bacterial activity. Sulfide oxidation produces sulfuric acid and an orange precipitate, ferric hydroxide (Fe(OH) 3 ), as summarised in Reaction(1) [9] . Once sulfides have been oxidised to sulfates, it is difficult to avoid oxidation of aqueous ferrous iron to ferric iron and subsequent iron hydroxide precipitation.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This process can be strongly catalysed by bacterial activity. Sulfide oxidation produces sulfuric acid and an orange precipitate, ferric hydroxide (Fe(OH) 3 ), as summarised in Reaction(1) [9] . Once sulfides have been oxidised to sulfates, it is difficult to avoid oxidation of aqueous ferrous iron to ferric iron and subsequent iron hydroxide precipitation.…”
Section: Results and Analysismentioning
confidence: 99%
“…In describing the results of Rio Tinto's review of AMD risk [3] , an important point was made that compliance with pertinent government regulations and permit conditions does not necessarily guarantee AMD is being managed in the most practical, robust and cost-effective manner. However, the history of global mining industry and practical experience have shown that acid metalliferous drainage exerted a hidden and cumulative influence on environment.…”
Section: Introductionmentioning
confidence: 99%
“…Rio Tinto have also embarked on an extensive risk review process that involved internal and external geochemical and hydrogeological experts visiting every Rio Tinto mine and project site with a significant potential AMD risk. Sites are initially screened using the Rio Tinto Hazard Screening Protocol to identify those mine sites with a significant potential AMD risk (Richards et. al.…”
Section: Corporate Guidancementioning
confidence: 99%